2022
DOI: 10.1007/s11255-022-03350-x
|View full text |Cite
|
Sign up to set email alerts
|

Does ICSI outcome in obstructive azoospermia differ according to the origin of retrieved spermatozoa or the cause of epididymal obstruction? A comparative study

Abstract: Purpose To determine whether ICSI outcomes are affected by sperm source or genital tract inflammatory status. Methods A retrospective cohort study was conducted in all consecutive obstructive azoospermia patients who underwent testicular sperm aspiration (TESA) or percutaneous epididymal sperm aspiration (PESA) and ICSI between February 1, 2017, and December 31, 2020. Couples were excluded if they were diagnosed with monogenic disease, abnormal karyotype, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Previous studies have evaluated the relationship between the use of surgically retrieved sperm and embryonic development through static morphological evaluation and the clinical outcomes of ICSI (Li et al, 2022(Li et al, , 2023Yu et al, 2022). Although the use of epididymal and testicular sperm does not compromise the clinical results of ICSI, one of the studies showed that the percentage of high-quality embryos is significantly greater for embryos derived from epididymal sperm than for those derived from testicular sperm (Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have evaluated the relationship between the use of surgically retrieved sperm and embryonic development through static morphological evaluation and the clinical outcomes of ICSI (Li et al, 2022(Li et al, , 2023Yu et al, 2022). Although the use of epididymal and testicular sperm does not compromise the clinical results of ICSI, one of the studies showed that the percentage of high-quality embryos is significantly greater for embryos derived from epididymal sperm than for those derived from testicular sperm (Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown comparable clinical outcomes between epididymal and ejaculated sperm (Nilsson et al, 2007). However, controversy remains regarding embryo quality assessed through conventional morphological classification (static observation) (Li et al, 2022(Li et al, , 2023Yu et al, 2022).…”
mentioning
confidence: 99%
“…When couples are infertile due to male factors, such as azoospermia, they often question the impact of surgical sperm retrieval on the pregnancy rate and birth rate. It may also present significant challenges for them to choose a method of assisted pregnancy, and some people will even give up the chance to have genetic offspring because of too much anxiety ( 9 ). Due to the progress of science and technology, surgical sperm retrieval has enabled more and more men with azoospermia to have offspring.…”
Section: Discussionmentioning
confidence: 99%
“…The general consensus favors epididymal sperm in cases of obstructive azoospermia (OA) with normal spermatogenesis [ 119 , 120 ], as they would have gone through the maturation process in the epididymis, where they acquire fertilizing ability [ 121 , 122 ]. Although studies showed that epididymal sperm have a higher fertilization rate [ 123 , 124 ] and clinical pregnancy rate [ 125 , 126 , 127 , 128 ] with OA patients when compared to testicular sperm in ICSI, possibly owing to the mature status of said spermatozoa, the overall statistics showed no significant difference between the two choices of sperm in OA patients [ 129 ]. An older study presented higher live birth rates when using epididymal sperm retrieved through microsurgical epididymal sperm aspiration (MESA) compared to Testicular Epididymal Sperm Extraction (TESE) [ 130 ], whereas newer retrospective studies showed higher live birth rates using testicular sperm but ultimately no significant difference between the two sperm sources in OA [ 124 , 126 , 128 ] and non-obstructive azoospermia (NOA) [ 127 ].…”
Section: Implications For Assisted Reproductive Technologymentioning
confidence: 99%
“…While congenital malformation including the cryptorchid testes, inguinal hernia and hypospadias had been reported in newborns from ICSI with testicular spermatozoa [ 131 , 132 ], studies showed no significant increase in birth defects between the use of testicular sperm and epididymal sperm [ 127 , 128 ], as well as between the use of testicular sperm and/or epididymal sperm and ejaculate sperm in ICSI [ 132 ].…”
Section: Implications For Assisted Reproductive Technologymentioning
confidence: 99%